I want to pay using my smartphone: lenses from the theory of diffusion of innovation and technological acceptance model / Oh Yit Leng … [et al.] - Leng, Oh Yit; M. S. Lam, Jason; Saw Chin, Khor; Woon, Chong Sin (Faculty of Accountancy, 2019)
Most research in both information systems and consumer behaviour fields have examined innovation adoption behaviour. However, little attention paid on other innovations such as smartphone retail consumption payment (mobile pay) by technological and consumer innovative behaviour theories. This study closes the research gap by conceptualising consumer adoption on mobile payment through the lenses of two theoretical models namely the theory of diffusion of innovation and technological acceptance model. The focus of the level of specificity of constructs proposed in this study setting adds a contribution to literature and having a more inclusive view in mobile payment adoption.We expect that the outcomes of the study will benefit the country, financial regulators, retail marketers as well as consumers.